The Integration of Open Educational Resources to the Mathematics Curriculum: Experiences of Students and Teachers of Secondary Education in Mexico - López Martínez, Edson; García Mejía, Irma Antonia; Gómez Zermeño, Marcela Georgina (Pedagogika, 2016)
This research studied the educational context of a Mexican private secondary school to determine the requirements that open learning environments and Learning Objects Repositories must fulfill to contribute to the Mathematics curriculum. A qualitative methodology was used with a case study design. For data recollection, semi-structured interviews were administrated to the students and teachers of a private secondary school to recollect information about their experiences with the virtual repository. The implementation of digital contents repository was initially a pilot project for the subject of Mathematics, and with the results it is expected to provide a wider panorama of the students’ needs and to reach the school’s vision to implement the repository to other subjects. The results show that students feel motivated to learn with interactive digital resources, and they feel safety, tranquility and reassurance because the repository provides a space that contributes to their learning process; meanwhile, teachers showed evidence of their experience to plan, design, implement and monitor the activities of Mathematics.